2015
DOI: 10.13189/ujibm.2015.030402
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Innovation and Organizational Performance in Construction Industry in Malaysia

Abstract: This paper aims to discuss the relationship between innovation and organizational performance in the construction industry. In Malaysia, the construction industry is known to be one of the industries that contribute significantly towards her economic growth. This contribution, more often than not is associated with the amount of innovation invested by organizations in the industry. The industry's innovation performance currently is reported to be amongst the lowest as compared to the others, which inspired thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 53 publications
3
23
0
Order By: Relevance
“…Leaders who have proactive behavior are more successful in facing dynamic environmental situations Thomas et al (2010) The results of the study Oni (2012); (Ashad et al, 2013;Wambugu et al, 2015) found that employee proactive behavior significantly affected business performance. Ashad et al (2013), Odumeru (2013), Mafini (2015), Tajudin et al (2015), and Karakas et al (2017); Soetantyo and Ardiyanti (2018) also found innovativeness had a significant effect on organizational performance Ashad et al (2013) also found that risk-taking significantly affected organizational performance. Based on this, the research hypothesis is constructed as follows: Hypothesis 1: Proactiveness has a significant positive effect on LPD performance Hypothesis 2: Innovativeness has a significant positive effect on LPD performance Hypothesis 3: risk-taking has a significant positive effect on LPD performance.…”
Section: Entrepreneurial Leadershipmentioning
confidence: 96%
See 1 more Smart Citation
“…Leaders who have proactive behavior are more successful in facing dynamic environmental situations Thomas et al (2010) The results of the study Oni (2012); (Ashad et al, 2013;Wambugu et al, 2015) found that employee proactive behavior significantly affected business performance. Ashad et al (2013), Odumeru (2013), Mafini (2015), Tajudin et al (2015), and Karakas et al (2017); Soetantyo and Ardiyanti (2018) also found innovativeness had a significant effect on organizational performance Ashad et al (2013) also found that risk-taking significantly affected organizational performance. Based on this, the research hypothesis is constructed as follows: Hypothesis 1: Proactiveness has a significant positive effect on LPD performance Hypothesis 2: Innovativeness has a significant positive effect on LPD performance Hypothesis 3: risk-taking has a significant positive effect on LPD performance.…”
Section: Entrepreneurial Leadershipmentioning
confidence: 96%
“…A number of previous research results that support the results of this study, such as Oni (2012); (Ashad et al, 2013); (Wambugu et al, 2015) found that employee proactive behavior significantly affected business performance. Ashad et al (2014); Odumeru (2013), Mafini (2015), and Tajudin et al (2015); Djampagau et al (2018); Soetantyo and Ardiyanti (2018) also found innovativeness had a significant effect on organizational performance. Ashad et al (2013) also found that risktaking significantly affected organizational performance.…”
Section: Hypothesis Testingmentioning
confidence: 98%
“…As defined by Proctor, Powell, and McMillen (2013), implementation of technology is a method or technique used by an organization to enhanced technology adoption, implementation and sustainability of technology usage practice. According to Tajuddin, Iberahim, and Ismail (2015), innovation in technology is one of the factors of innovation success. Through innovation in technology, a process that is not practical anymore will be replaced with a new process.…”
Section: Innovation Success Factorsmentioning
confidence: 99%
“…According to Ali et al (2013), several research works have been undertaken on performance measurement at the project level. Recent studies now concentrate on performance evaluation and management at the company level (Tajuddin et al , 2015; Ali et al , 2015). To achieve organisational goals, most firms have tried to improve their efficiency to enhance their performance (Rathore, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve organisational goals, most firms have tried to improve their efficiency to enhance their performance (Rathore, 2016). Tajuddin et al (2015), posited that globalisation offers both opportunities and challenges in which organisations are compelled to make drastic enhancements not just to compete but to survive. Sonson et al (2017) in their studies affirmed that the dynamism and competition associated with the business environment have motivated and forced construction firms to enforce modern performance measurement and management systems and structures to create more comprehensive information on their performance.…”
Section: Introductionmentioning
confidence: 99%